Pengelolaan Supervisi Akademik Di SMPN 1 Todanan Blora - Wiwin Wahyuningsih; Sofyan Anif (Manajemen Pendidikan, 2016)
The aim of this study to describe the planning, implementation, feedback and follow-up of the academic supervision at Junior High School 1 Todanan Blora. This study includes qualitative research with ethnographic design. Research is located at Junior High School 1 Todanan Blora. The study begins from July 2015 to January 2016. The subjects of the research are principal, vice principal of curriculum, teachers of subjects. The technique of collecting data through observation, in-depth interviews, and documentation. The interview process uses first order understanding and second order understading. The validity of the data with simber triangulation of source, triangulation techniques, and triangulation of time. Data analysis technique uses flow method. The results of the study (1) The planning process of supervision contains making supervision schedule and assessment instruments of supervision conducted by the principal and vice principal of curriculum, (2) The implementation of academic supervision is carried out with the preparation of supporting supervision documents and continue with classroom observation by supervisors, (3) Feedback process of supervision is done by evaluating the academic supervision, as well as providing a solution to solve the problem experienced by teachers in teaching, (4) The follow-up of supervision is done by supervisor continuously and providing the opportunity for teachers to follow training activities to improve their capability of teaching.